Metacognitive thinking and its relationship to self-esteem among students of King Abdullah II Schools for Excellence in Jordan - Al-Rbehat, Eman Majed (Journal of Educational and Psychological Sciences, 2022)
This study aimed to reveal the level of metacognitive thinking and self-esteem and the relationship between them among students of King Abdullah II Schools for Excellence in Jordan. The sample of the study, which was selected in a stratified random manner, consisted of (221) male and female students from high school and upper basic stage, 126 males and (95) females. And to achieve the goals of this study the researcher developed two tools to be used in the study, the first one is used to measure the level of metacognitive thinking and the second one is used to measure the level of self-esteem. The results showed a positive, statistically significant relationship between the metacognitive thinking scale and self-esteem, and the results indicated that there were no statistically significant differences on the metacognitive thinking scale depending on the gender, academic level and student average, while the results indicated that there were no significant differences statistical level of self-esteem according to the variables of the school stage and the average, and the presence of statistically significant differences according to the gender variable, with males outperforming females. At the end of the study, a number of recommendations were noted, most notably the implementation of workshops and training programs for teachers on teaching strategies that contribute to the development of metacognitive thinking skills and self-esteem among students at all levels of education.